Direct Measurement of the Direction, Size, and Velocity of Droplets Generated by Top‐Blowing. Issue 9 (21st June 2019) - Haas, Tim; Ringel, Aron; Visuri, Ville-Valtteri; Eickhoff, Moritz; Pfeifer, Herbert
Abstract : Problems associated with top‐blowing are present in most steel plants. While it promotes high reaction rates, it can cause loss of yield, working hazards, and increased maintenance cost by spitting, skulling, or lid sticking. Although the basic physics of the splashing phenomenon have already been established, earlier studies have not addressed the velocities of splashing droplets. Furthermore, existing information on the size and impingement angle of the droplets is based on indirect measurements. Herein, a direct measurement method for splashing droplets is developed that obtains the number of droplets, splashing angle, droplet velocity, and diameter at the same time. It is found that existing correlations overestimate the droplet diameter, because they are biased by the indirect method and overfit the results obtained with raw iron. Grid measurements indicate that all droplet properties strongly depend upon the sampling position. Finally, the splashing angle is found to become steeper while the lance height decreases. However, the effect is less correlated with the cavity mode than assumed in the literature. Further measurements are proposed, using the methodology developed in this work, to derive more comprehensive droplet property correlations. By that, lance designs and blowing practices can be optimized. Abstract : A novel measurement technique is developed to analyze splashing droplets while top‐blowing in a water model. Simultaneously, the droplet size, velocity, number, and direction are recorded for different measurement positions and lance configurations. The results reveal a bias in existing correlations and yield splashing trajectories for different blowing numbers.